THE INFLUENCE OF GREEN HUMAN RESOURCE MANAGEMENT AND CULTURAL VALUE INTEGRATION ON SUSTAINABLE BUSINESS PERFORMANCE OF MSMES IN THE CULTURAL TOURISM SECTOR IN BALI (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
This study aims to analyze the influence of Green Human Resource Management (GHRM) and Cultural Value Integration (CVI) on Sustainable Business Performance (SBP) in MSMEs in the cultural tourism sector in Bali. A quantitative approach with an explanatory causal design was used, involving 60 respondents selected using purposive sampling with the criteria of active involvement in MSME management. Data were collected through a questionnaire with a Likert scale of 1–5 and analyzed using SEM-PLS through SmartPLS. The results showed that GHRM had a positive and significant effect on SBP, CVI had a positive and significant effect on SBP, and GHRM and CVI simultaneously contributed positively to increasing SBP. These findings emphasize the importance of environmentally friendly HR management practices and the integration of local cultural values as strategies to strengthen the sustainability of cultural tourism MSMEs. The implications of this study provide recommendations for MSME managers to strengthen environmentally-based HR policies and utilize Balinese cultural values in business strategies.
Keywords: green human resource management; cultural value integration; sustainable business performance; MSMEs; cultural tourism